Hydrolytic Exoenzymes Produced by Bacteria Isolated and Identified From the Gastrointestinal Tract of Bombay Duck - Hossain, Tanim J.; Chowdhury, Sumaiya I.; Mozumder, Halima A.; Chowdhury, Mohammad N. A.; Ali, Ferdausi; Rahman, Nabila; Dey, Sujan (Frontiers in Microbiology, 2020)
Bacteria producing hydrolytic exoenzymes are of great importance considering their contribution to the host metabolism as well as for their various applications in industrial bioprocesses. In this work hydrolytic capacity of bacteria isolated from the gastrointestinal tract of Bombay duck (Harpadon nehereus) was analyzed and the enzyme-producing bacteria were genetically characterized. A total of twenty gut-associated bacteria, classified into seventeen different species, were isolated and screened for the production of protease, lipase, pectinase, cellulase and amylase enzymes. It was found that thirteen of the isolates could produce at least one of these hydrolytic enzymes among which protease was the most common enzyme detected in ten isolates; lipase in nine, pectinase in four, and cellulase and amylase in one isolate each. This enzymatic array strongly correlated to the previously reported eating behavior of Bombay duck. 16S rRNA gene sequence-based taxonomic classification of the enzyme-producing isolates revealed that the thirteen isolates were grouped into three different classes of bacteria consisting of eight different genera. Staphylococcus, representing ~46% of the isolates, was the most dominant genus. Measurement of enzyme-production via agar diffusion technique revealed that one of the isolates which belonged to the genus Exiguobacterium, secreted the highest amount of lipolytic and pectinolytic enzymes, whereas a Staphylococcus species produced highest proteolytic activity. The Exiguobacterium sp. expressing a maximum of four hydrolases, appeared to be the most promising isolate of all.